Plasma Free Amino Acids and Risk of Cardiovascular Disease in Chinese Patients With Type 2 Diabetes - Li, Tie; Luo, Hui-Huan; Feng, Xiao-Fei; Bai, Yu; Fang, Zhong-Ze; Wu, Gui-Gang; Wu, Jian-Lin (Frontiers in Endocrinology, 2021)
Objectives: This study aimed to explore associations between plasma free amino acids (PFAA) and risk of cardiovascular disease (CVD) in Chinese with Type 2 diabetes (T2D). Methods: We retrieved 741 inpatients with T2D consecutively from tertiary hospital. 23 PFAA were measured. CVD was defined as having coronary heart disease (CHD) or stroke. Principal component analysis was used to extract factors of PFAA. Factors and their components were introduced into binary logistic regressions as continuous and tertiles to obtain OR (odds ratio) and 95% Confidence interval (CI) for CVD (or its components) risk. Results: Of 741 inpatients, 282 (38.1%) had CVD (CHD alone: 122, stroke alone: 109, both: 51). Five factors were extracted, accounting for 65% of the total variance. Factor 3 composed of glutamate and tryptophan was associated with increased CVD risk (ORs, 95%CI of top vs. bottom tertiles: 1.60, 1.02-2.50 for CVD; 2.19, 1.17-4.07 for stroke, 1.51, 0.83-2.73 for CHD); the ORs (top vs. bottom tertiles) of glutamate were 2.62 (95%CI, 1.18-5.84) for stroke and 1.44 (0.80-2.61) for CHD. the ORs (top vs. bottom tertiles) of tryptophan were 1.50 (0.81-2.75) for stroke and 1.07 (0.58-1.97) for CHD. Comparable results were observed according to important confounders (all P for interaction >0.05). Conclusions: Elevated factor 3 composed of glutamate and tryptophan was associated with increased CVD ,especially stroke in T2D in China.